2020
DOI: 10.1021/acscentsci.0c00855
|View full text |Cite|
|
Sign up to set email alerts
|

The SARS-COV-2 Spike Protein Binds Sialic Acids and Enables Rapid Detection in a Lateral Flow Point of Care Diagnostic Device

Abstract: There is an urgent need to understand the behavior of the novel coronavirus (SARS-COV-2), which is the causative agent of COVID-19, and to develop point-of-care diagnostics. Here, a glyconanoparticle platform is used to discover that N -acetyl neuraminic acid has affinity toward the SARS-COV-2 spike glycoprotein, demonstrating its glycan-binding function. Optimization of the particle size and coating enabled detection of the spike glycoprotein in lateral flow and showed selectivity over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
282
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 261 publications
(288 citation statements)
references
References 52 publications
(88 reference statements)
5
282
0
1
Order By: Relevance
“…As high purity was required, all glycans were subjected to a two-step purication (gel ltration and ash or anion-exchange chromatography). In total, eight uorinated disaccharides (16)(17)(18)(19)(20)(21)(22)(23) bearing azidopropyl linkers were prepared, in addition to lacto-N-biose derivative (15), in isolated yields ranging from 25-76%.…”
Section: Resultsmentioning
confidence: 99%
“…As high purity was required, all glycans were subjected to a two-step purication (gel ltration and ash or anion-exchange chromatography). In total, eight uorinated disaccharides (16)(17)(18)(19)(20)(21)(22)(23) bearing azidopropyl linkers were prepared, in addition to lacto-N-biose derivative (15), in isolated yields ranging from 25-76%.…”
Section: Resultsmentioning
confidence: 99%
“…Baker et al [31] reported the synthesis of polymerstabilized multivalent gold nanoparticles bearing sialic acid derivative and their interaction with spike glycoprotein. It was observed that α, N-acetylneuraminic acid binds strongly Table 1.…”
Section: Nano-based Detection Methodsmentioning
confidence: 99%
“…Lateral flow assay for virus using glycan capture units (adapted from Baker et al[31]; reuse is permitted under CC BY-NC 4.0 license).…”
mentioning
confidence: 99%
“…Applying these characteristics has the advantage of building a low-cost detection platform that can be detected in less than 30 minutes with a lateral flow diagnostic device. 277 …”
Section: Application Of Nanotechnology In Covid-19 Therapeuticsmentioning
confidence: 99%